Analisis Kinerja Jaringan Irigasi - Fatchan Nurrochmad (agriTECH, 2007)
The performance of long-lasting irrigation network depends on various factors. They are non-physical factors (management, operation and maintenance cost unit) andphysical factors (water availability and irrigation infrastructure). The assessment to the performance of irrigation network was carried out by interviewing the management, analyzing the operation and maintenance cost unit (non-physical factor) and evaluating the infrastructure condition of the irrigation network (physical factor, including water availability) by having consistent guidance on the cropping pattern application. Based on the three factors, the command areas with area more than 500 ha (ranked from 1 to 4) indicated good performance and the others are moderate. Such condition implied that the Government of Kabupaten Purworejo paid significant attention upon the management of command area with areamore than 500 ha. Stabilizing Tegalduren command area to become technical was necessary in order to support the participative irrigation management. It is necessary to continually build up the farmers’ capability to cope with their powerlessness problem in maintaining the irrigation infrastructure based on the priority (demand-driven).ABSTRAKKinerja jaringan irigasi lestari tergantung pada beberapa faktor. Faktor pengaruh tersebut berupa faktor non fisik (pengelola dan ketersediaan biaya operasi dan pemeliharaan) dan fisik (ketersediaan air dan prasarana jaringan). Penilaian terhadap kinerja jaringan irigasi dilakukan dengan wawancara terhadap pengelola dan analisis biaya satuan operasi dan pemeliharaa (faktor non fisik) dan evaluasi kondisi prasarana jaringan irigasi (fisik, termasuk ketersediaan air) dengan panduan penerapan pola dan tata tanam secara konsisten. Berdasarkan 3 faktor tersebut daerah irigasi (DI) dengan luas lebih dari 500 ha (ranking 1 sampai dengan 4) menunjukkan kinerja yang baik dan yang lain cukup baik. Kondisi tersebut menyiratkan bahwa Pemerintah Kabupaten Purworejo mempunyai atensi yang besar dalam pengelolaan DI dengan luas lebih dari 500 ha. Pemantapan DI Tegalduren menjadi DI teknis perlu dilakukan untuk menunjang kegiatan pengelolaan irigasi partisipatif. Ketidakberdayaanpetani dalam pemeliharaan prasarana irigasi perlu dibina secara terus menerus berdasarkan skala prioritas (demand–driven).